The relationship between thermal insulation and heat source in shaping the energy efficiency of residential buildings: a case study of Poland - Biała, Aneta (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
The energy efficiency of residential buildings results from the complex interplay of thermal insulation parameters of building envelopes, ventilation systems, and heat sources. This article examines these interdependencies in the context of reducing the EP (primary energy) index, considering the standards effective from 2021. The study highlights that improving the thermal insulation of external walls plays a pivotal role in lowering the EP index, surpassing the effects of roof or ground floor insulation. The findings reveal that the benefits of reducing the U-value vary depending on the heat source. The greatest savings were observed in buildings with electric heating, while buildings equipped with heat pumps showed limited benefits due to their high efficiency (COP). Furthermore, the application of mechanical ventilation improves a building’s energy performance, particularly when combined with traditional heat sources. In contrast, its impact is minimal in buildings with heat pumps. The results emphasise the importance of an integrated approach to building design, accounting for the interactions between envelope insulation, ventilation systems, and heat sources. It is recommended to optimise thermal parameters and invest in modern heating and ventilation technologies to achieve significant energy savings and meet stringent climate requirements.